Analisis Kualitas Sistem E-Rapor SP Menggunakan Metode WebQual 4.0 dan IPA - Gusti Ayu Mas Ekayanti; Gede Arna Jude Saskara; I Nyoman Tri Anindia Putra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
One form of information technology implementation in education is the use of the e-Rapor SP system in preparing students’ learning outcome reports. However, users still experience various difficulties in its implementation, indicating that the system quality needs improvement. This study aims to measure the quality of the e-Rapor SP system at the junior high school level based on users’ perceptions in Buleleng Regency and to identify low-performing aspects for improvement recommendations. System quality was measured using the WebQual 4.0 variables, including usability, information quality, service interaction quality, and overall impression. This study employed a quantitative approach using a survey method. Data were collected from 84 respondents through a WebQual 4.0-based questionnaire and analyzed using descriptive statistics, the WebQual Index, and Importance Performance Analysis (IPA). The results show that the e-Rapor system is perceived as having good quality but has not yet met users’ expectations. The WebQual Index value of 0.78 indicates a good but not ideal level of system quality. Gap and conformity analyses revealed negative gaps and conformity values below 100%, indicating a mismatch between system performance and user expectations. The recommended improvements focus on enhancing service quality through clearer helpdesk support or guidance, as well as faster and more consistent service responses. The findings of this study provide a basis for decision-making to improve the quality of the e-Rapor system.